Factors Contributing to English as a Foreign Language Learners’ Academic Burnout: An Investigation Through the Lens of Cultural Historical Activity Theory - Bui, Quyen Thi Thuc; Bui, Thanh Do Cong; Nguyen, Quang Nhat (Frontiers in Education, 2022)
During the shift from face-to-face to online emergency classes due to the Covid-19 pandemic, learners of English as a Foreign Language (EFL) are under constant pressure to familiarize themselves with the once-in- many-generation learning context. Based on the cultural historical activity theory (CHAT), this qualitative study investigated factors contributing to EFL learners' academic burnout at Open University, Vietnam. The interviewees were seven students recruited using the theoretical-based sampling technique. The data translation consisted of iterative rounds of interviews which lasted approximately 60 minutes each until the data saturation point is reached. The content analysis revealed six factors that impacted EFL learners' physical and psychological exhaustion, including prolonged online learning time, privacy concerns and cyber-bullying, teachers' role, institution's role, and support community outside the classroom. Also, teachers' insufficient preparation for online teaching and students' academic misconduct during exams were factors that created EFL learners' academic cynicism. Finally, participation in social networking sites' extracurricular activities, participation checking, and cheating in exams affected the last dimension of academic burnout, a sense of academic achievement. Based on this study, the authority, administrators, and teachers can take a more proactive role in supporting students in curbing their academic burnout during this unprecedented pandemic. The authors also hope that this study can lay the foundation for further humanistic research into the EFL learner’s psychological world in online classes, particularly when each student's social cultural background is considered.